Frontiers in human factors: embedding specialists in multi-disciplinary efforts to improve healthcare - Catchpole, Ken (Int J Qual Health Care, 2020)
Despite the application of a huge range of human factors (HF) principles in a growing range of care contexts, there is much more that could be done to realize this expertise for patient benefit, staff well-being and organizational performance. Healthcare has struggled to embrace system safety approaches, misapplied or misinterpreted others, and has stuck to a range of outdated and potentially counter-productive myths even has safety science has developed. One consequence of these persistent misunderstandings is that few opportunities exist in clinical settings for qualified HF professionals. Instead, HF has been applied by clinicians and others, to highly variable degrees—sometimes great success, but frequently in limited and sometimes counter-productive ways. Meanwhile, HF professionals have struggled to make a meaningful impact on frontline care and have had little career structure or support. However, in the last few years, embedded clinical HF practitioners have begun to have considerable success that are now being supported and amplified by professional networks. The recent coronavirus disease of 2019 (COVID-19) experiences confirm this. Closer collaboration between healthcare and HF professionals will result in significant and ultimately beneficial changes to both professions and clinical care.